Determination Of Lead And Cadmium Metal Content In Rambai Leaf Simplicia (Baccaurea Motleyana Müll.Arg.) Using Atomic Absorption Spectrophotometry Method - Aqila Widya Sari; Rahmat Hidayat; Tiara Ajeng Listyani (International Journal of Health Engineering and Technology, 2026)
Rambai leaf (Baccaurea motleyana Müll. Arg.) is traditionally used to treat smallpox, diarrhea, and bruises, but it has the potential to be contaminated with heavy metals such as lead (Pb) and cadmium (Cd) which are toxic and accumulative. This study aims to determine the levels of Pb and Cd in rambai leaf and compare them with the safe limits of BPOM RI and WHO. The type of research is descriptive quantitative with Atomic Absorption Spectrophotometry (AAS) method using an air-acetylene flame system. The study population was all rambai plants in Nanga Kantuk Village, West Kalimantan, with purposive sampling. The main instrument was SSA contrAA 800, while data analysis was carried out through a linear calibration curve (R> 0.998), regression, and calculation of levels (mg/kg). The results showed Pb levels of 4.29 mg/kg and Cd <LOD (0.0131 mg/L). These results indicate that Pb metal was detected, while Cd was not detected quantitatively. In conclusion, the levels of Pb and Cd in rambai leaf simplicia are still below the safe limits of BPOM RI (Pb ≤ 10 mg/kg; Cd ≤ 0.3 mg/kg), so it is safe to use as a traditional medicine ingredient from the aspect of heavy metal contamination.